Evolutionary implications of a new transitional blastozoan echinoderm from the middle Cambrian of the Czech Republic. (23rd March 2017) - Nardin, Elise; Lefebvre, Bertrand; Fatka, Oldřich; Nohejlová, Martina; Kašička, Libor; Šinágl, Miroslav; Szabad, Michal
Abstract: The primitive blastozoan Felbabkacystis luckae n. gen. n. sp. is described from the Drumian Jince Formation, Barrandian area (Czech Republic) from eleven fairly well-preserved specimens. Its unique body plan organization is composed of a relatively long, stalk-like imbricate structure directly connected to the aboral imbricate cup of the test and of an adoral vaulted tessellate test supporting the ambulacral and brachiolar systems. Its bipartite test, called prototheca, highlights the evolution of the body wall among blastozoans. Felbabkacystis n. gen. shows the combination of plesiomorphic (imbricate stalk-like appendage) and derived features (highly domed peristome, elongate epispires). The new genus is interpreted as a transitional form between calyx-bearing and theca-bearing blastozoans, and is attributed to the new family Felbabkacystidae. The lithology, the associated fauna, and the possession of a long stalk suggest that Felbabkacystis was probably a low-level suspension feeder living in relatively deep settings.